The Seasonal Distribution of Suspended Particles and Their Iron and Manganese Loading in a Glacial Runoff Fiord - Syvitski, J.; Lewis, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1992)
Summary Three mechanisms are responsible for the distribution of inorganic suspended particulate matter in a glacially influenced fiord suchas Knight Inlet, British Columbia. The most important is the influx of sediment from rivers draining hinterland ice fields, with maximum input levels reached in the summer melt season and during the autumn period of flashfloods. Sediment can also enter a fiord from the sea: 1) within the return flow of estuarine circulation that is fully developed during the late spring through early autumn, and 2) aspart of deep shelf water that exchanges and flushes out the deep water of the fiord basin, particularly during the winter season. The third mechanism for sediment accumulating on the sea floor is through the action of episodic turbidity currents. These sediment gravity flows carry coarse delta-front sediments to the otherwise muddy basin floor. The relative abundance of particulate iron within the suspended sediment load directly relates to higher levels of iron in glacially derived particles issuing from river mouths atthe head of the fiord. Elevated levels of particulate manganese may be a result of turbidity currents. They are observed in the water column nearest the sea floor where circulation and geochemical conditions would normally preclude their existence.